Phosphogypsum-based fine aggregate, and preparation method and application thereof
Patent Information
- Application Number
- CN202512059114.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-31
AI Technical Summary
然而,上述制备方法制得的磷石膏基骨料的28d筒压强度最高为5.23MPa,筒压强度仍较低
[0015]本发明提供了一种磷石膏基细骨料的制备方法,包括以下步骤:将磷石膏、钙基碱性材料、矿渣和水混合,得到湿料;将所述湿料进行双辊压制成球,得到压制料;将所述压制料进行养护,得到磷石膏基细骨料;所述磷石膏基细骨料的粒径为1~4mm。传统的磷石膏骨料采用成球盘依靠滚动造粒,通过压力制备,需要在压制成试块后破碎,容易在破碎的过程中引入微裂纹,增加缺陷,降低骨料强度。而本发明将磷石膏、钙基碱性材料和矿渣复配使用,钙基碱性材料对矿渣产生碱性激发,促进矿渣的快速溶解,参与水化反应;磷石膏中的硫酸盐(二水硫酸钙)对矿渣实现硫酸盐激发产生胶凝性,矿渣中存在大量非晶体相,使骨料在碱性和盐的复合激发下逐渐水化,形成C-(A)-S-H凝胶(C-A-S-H凝胶或C-S-H凝胶,其中C为氧化钙,A为氧化铝,S为氧化硅,H为水)和钙矾石(AFt),为磷石膏基细骨料提供了主要强度,在养护过程中磷石膏基细骨料会继续缓慢水化,进一步提高强度,实施例制得的磷石膏基细骨料的筒压强度高达12.8MPa。而且,本发明制得的磷石膏基细骨料的粒径为1~4mm,相对于粗骨料粒径更小,比表面积更大,制得的磷石膏基细骨料相对于粗骨料具有更高的强度和更低的吸水率。而且,本发明采用加压双辊压制成球(压力为15~20MPa)的方式,提高了磷石膏基细骨料的密实度,可连续不间断的制备磷石膏基细骨料,提高了生产效率,平均产量高达1t/h(1吨/小时),适宜工业化生产。进一步的,磷石膏中二水硫酸钙颗粒较大且外表面光滑致密,吸水性较差,本发明通过对磷石膏进行粉磨,粉磨后的磷石膏比表面积增大,具有高吸水性,在磷石膏基细骨料中可以作为水的通道,实现水化后期骨料内部内养护的水分补充,通过内部自反应进一步提高了磷石膏基细骨料的强度。而且,本发明在低水灰比(水灰比为0.09~0.11)的基础上采用高压力(压力为15~20MPa)压制成球,制得的磷石膏基细骨料的骨料密实度显著提高。
Smart Images

Figure CN121850420B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a phosphogypsum-based fine aggregate, its preparation method, and its application. Background Technology
[0002] Phosphogypsum is an industrial byproduct generated during the production of phosphoric acid in phosphate plants. It is produced in large quantities, stored in large quantities, and is difficult to utilize comprehensively. The main components of phosphogypsum are calcium sulfate dihydrate, quartz, and phosphates, with a pH of 2-3, indicating it is acidic. By processing phosphogypsum into phosphogypsum-based aggregates and applying them to concrete, the problem of phosphogypsum resource utilization can be effectively solved.
[0003] Traditional phosphogypsum-based aggregates are mainly produced through pelletizing using a pelletizing disc. While the resulting aggregates have high sphericity, they suffer from low density, making them difficult to compact and resulting in low strength. Furthermore, this method can only produce coarse aggregates, not fine ones. A related technology discloses a method for preparing high-density phosphogypsum-based aggregates. This method involves mixing modified phosphogypsum, ultrafine slag powder, silicate cement, metakaolin, and water to form a rigid mixture. This mixture is then extruded and shaped using smooth rollers, longitudinally grooved rollers, and transversely grooved rollers, followed by curing to obtain high-density phosphogypsum-based aggregates. However, the 28-day compressive strength of the phosphogypsum-based aggregates prepared by this method is only a maximum of 5.23 MPa, which is still relatively low. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a phosphogypsum-based fine aggregate, its preparation method, and its application. The phosphogypsum-based fine aggregate prepared by the method provided by this invention has a compressive strength as high as 12.8 MPa.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing phosphogypsum-based fine aggregate, comprising the following steps: Phosphogypsum, calcium-based alkaline materials, slag, and water are mixed to obtain a wet material; The wet material is pressed into balls using two rollers to obtain pressed material; The pressed material is cured to obtain phosphogypsum-based fine aggregate; The particle size of the phosphogypsum-based fine aggregate is 1~4mm; The pressure at which the twin rollers press the balls is 15~20MPa.
[0006] Preferably, the phosphogypsum has a particle size of 1~4.75mm and a specific surface area of 200~220m². 2 / kg.
[0007] Preferably, the calcium-based alkaline material includes one or more of calcium hydroxide, calcium oxide, carbide slag, red mud, and alkaline slag; The mass ratio of the phosphogypsum to the calcium-based alkaline material is 2~2.5:1; The mass ratio of phosphogypsum to slag is 6:30~31.
[0008] Preferably, the mass ratio of the total mass of the phosphogypsum, calcium-based alkaline material and slag to the mass of water is 10:0.9~1.1.
[0009] Preferably, the temperature at which the two rollers press the balls is 15~25℃ and the pressure is 15~20MPa.
[0010] Preferably, the curing temperature is 18~22℃, the relative humidity is ≥95%, and the time is 3~28 days.
[0011] Preferably, mixing phosphogypsum, calcium-based alkaline material, slag, and water includes the following steps: Phosphogypsum, calcium-based alkaline materials, and slag are mixed to obtain a powder. Water is sprayed into the powder to obtain a wet material.
[0012] Preferably, the phosphogypsum is further subjected to drying and grinding in sequence before use; The drying temperature is 60~80℃, and the time is 1200~1680min; The grinding time is 5-15 minutes.
[0013] The present invention provides a phosphogypsum-based fine aggregate prepared by the preparation method described in the above technical solution.
[0014] This invention provides the application of the phosphogypsum-based fine aggregate described in the above technical solution in building materials.
[0015] This invention provides a method for preparing phosphogypsum-based fine aggregate, comprising the following steps: mixing phosphogypsum, calcium-based alkaline materials, slag, and water to obtain a wet material; pressing the wet material into pellets using a double roller to obtain a pressed material; and curing the pressed material to obtain the phosphogypsum-based fine aggregate; wherein the particle size of the phosphogypsum-based fine aggregate is 1-4 mm. Traditional phosphogypsum aggregate is prepared by rolling granulation using a pelletizing disc under pressure, requiring crushing after pressing into test blocks. This crushing process easily introduces microcracks, increasing defects and reducing aggregate strength. This invention combines phosphogypsum, calcium-based alkaline materials, and slag. The calcium-based alkaline materials induce alkaline activation in the slag, promoting its rapid dissolution and participation in the hydration reaction. The sulfate (calcium sulfate dihydrate) in the phosphogypsum induces sulfate activation in the slag, producing a gelling effect. The slag contains a large amount of amorphous phase, which causes the aggregate to gradually hydrate under the combined activation of alkalinity and salt, forming C-(A)-SH gel (CASH gel or CSH gel, where C is calcium oxide, A is aluminum oxide, S is silicon dioxide, and H is water) and ettringite (AFt), which provides the main strength for the phosphogypsum-based fine aggregate. During the curing process, the phosphogypsum-based fine aggregate continues to hydrate slowly, further increasing its strength. The compressive strength of the phosphogypsum-based fine aggregate obtained in the example is as high as 12.8 MPa. Furthermore, the phosphogypsum-based fine aggregate obtained by this invention has a particle size of 1-4 mm, which is smaller than that of coarse aggregate, resulting in a larger specific surface area. This leads to higher strength and lower water absorption compared to coarse aggregate. Moreover, the invention employs a double-roller pressing method (pressure 15-20 MPa) to form spheres, improving the density of the phosphogypsum-based fine aggregate. This allows for continuous and uninterrupted production, increasing production efficiency with an average output of up to 1 t / h, suitable for industrial production. Further, while calcium sulfate dihydrate particles in phosphogypsum are relatively large and have a smooth, dense surface, resulting in poor water absorption, this invention addresses this by grinding the phosphogypsum. The resulting phosphogypsum has an increased specific surface area and high water absorption, acting as a water channel within the phosphogypsum-based fine aggregate. This facilitates internal water replenishment during the later stages of hydration, further enhancing the strength of the phosphogypsum-based fine aggregate through internal self-reaction. Moreover, the present invention uses high pressure (15-20 MPa) to press the phosphogypsum-based fine aggregate into balls based on a low water-cement ratio (0.09-0.11), which significantly improves the aggregate density. Attached Figure Description
[0016] Figure 1 This is a flowchart illustrating the preparation of phosphogypsum-based fine aggregate in Example 1; Figure 2 This is an image showing the appearance of the phosphogypsum-based fine aggregate in Example 1 after 28 days of curing. Figure 3 This is a scanning electron microscope image of the phosphogypsum-based fine aggregate in Example 1 after 28 days of curing; Figure 4 The images show X-ray diffraction patterns of aggregates of different particle sizes in the phosphogypsum-based fine aggregate in Example 1. In Figure (a), the curing time is 3 days, and in Figure (b), the curing time is 28 days. Figure 5 The figures are TG diagrams of aggregates of different particle sizes in the phosphogypsum-based fine aggregate in Example 1. Figure (a) shows the curing time for 3 days, and Figure (b) shows the curing time for 28 days. Detailed Implementation
[0017] This invention provides a method for preparing phosphogypsum-based fine aggregate, comprising the following steps: Phosphogypsum, calcium-based alkaline materials, slag, and water are mixed to obtain a wet material; The wet material is pressed into balls using two rollers to obtain pressed material; The pressed material is cured to obtain phosphogypsum-based fine aggregate; The particle size of the phosphogypsum-based fine aggregate is 1~4mm.
[0018] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0019] This invention involves mixing phosphogypsum, calcium-based alkaline materials, slag, and water to obtain a wet material.
[0020] In this invention, the particle size of the phosphogypsum can be 1~4.75 mm, specifically 1 mm, 2 mm, 3.5 mm or 4.75 mm; the specific surface area of the phosphogypsum can be 200~220 m². 2 / kg, which can be specifically 200m 2 / kg, 204m 2 / kg, 207m 2 / kg, 210m 2 / kg, 215m 2 / kg or 220m 2 / kg. In this invention, the phosphogypsum may further include drying and grinding sequentially before use. In this invention, the drying can specifically be oven drying; the drying temperature can be 60~80℃, specifically 60℃, 65℃, 70℃, 75℃ or 80℃; the drying time can be 1200~1680min, specifically 1200min, 1400min, 1550min or 1680min; the grinding time can be 5~15min, specifically 5min, 8min, 10min, 12min or 15min. This invention does not specifically limit other grinding parameters; conventional grinding methods in the art can be used to achieve a particle size of 1~4.75mm for the phosphogypsum. This invention involves grinding phosphogypsum, which increases its specific surface area and enhances its water absorption. In phosphogypsum-based fine aggregates, it can act as a water channel, enabling the replenishment of moisture for internal curing of the aggregates during the later stages of hydration. Through internal self-reaction, it further improves the strength of the phosphogypsum-based fine aggregates.
[0021] In this invention, the calcium-based alkaline material may include one or more of calcium hydroxide, calcium oxide, carbide slag, red mud, and alkaline slag; the mass ratio of phosphogypsum to calcium-based alkaline material may be 2~2.5:1, specifically 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, or 2.5:1; the mass ratio of phosphogypsum to slag may be 6:30~31, specifically 6:30, 6:30.2, 6:30.4, 6:30.6, 6:30.8, or 6:31; the mass ratio of the total mass of phosphogypsum, calcium-based alkaline material, and slag to the mass of water may be 10:0.9~1.1, specifically 10:0.9, 10:0.95, 10:1, 10:1.05, or 10:1.1.
[0022] In this invention, mixing phosphogypsum, calcium-based alkaline materials, slag, and water specifically includes the following steps: mixing phosphogypsum, calcium-based alkaline materials, and slag (referred to as the first mixing) to obtain a powder; spraying water into the powder to obtain a wet material. In this invention, the first mixing time can be 5-10 minutes, specifically 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, or 10 minutes. The diameter of the water droplets formed during the water spraying process can be <200 μm, or 100-150 μm, specifically 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, or 150 μm; the outlet flow velocity of the nozzle used for water spraying can be 10-15 m / s, specifically 10 m / s, 11 m / s, 12 m / s, 13 m / s, 14 m / s, or 15 m / s.
[0023] After obtaining the wet material, the present invention uses two rollers to press the wet material into balls to obtain pressed material.
[0024] In this invention, the double-roller spheroidizing process can be carried out in a double-roller extrusion spheroidizing machine. The temperature for double-roller spheroidizing can be 15~25℃, specifically 15℃, 18℃, 20℃, 22℃, or 25℃. The pressure for double-roller spheroidizing is 15~20MPa, specifically 15MPa, 16MPa, 17MPa, 18MPa, 19MPa, or 20MPa. During the double-roller spheroidizing process, the rotational speed of the disc in the double-roller extrusion spheroidizing machine can be 40~45rpm, specifically 40rpm, 41rpm, 42rpm, 43rpm, 44rpm, or 45rpm. This invention does not specifically limit the spacing between the two rollers of the double-roller extrusion spheroidizing machine; the spacing only needs to be sufficient to achieve a spheroidizing pressure of 15~20MPa. This invention does not specifically limit the shape of the pressed material; the shape is based on the shape of the grooves on the two rollers, and can specifically be elongated, spherical, or oblate. In this invention, the diameter of the groove can be specifically 1-2 mm, 2-3 mm, 3-4 mm, or 4-4.75 mm. This invention does not have a specific limitation on the mass of the wet material added in a single batch; the higher the rotational speed of the disc in the roller extrusion pelletizing machine, the higher the mass of the wet material added in a single batch, which can be 13-17 kg, specifically 13 kg, 14 kg, 15 kg, 16 kg, or 17 kg. This invention uses high pressure (15-20 MPa) to press the phosphogypsum-based fine aggregate into pellets based on a low water-cement ratio (0.09-0.11), resulting in significantly improved aggregate density and a cylinder compressive strength as high as 12.8 MPa. Furthermore, the phosphogypsum-based fine aggregate further improves its strength through internal self-reaction. This is lower than the pressure required to achieve a comparable cylinder compressive strength in existing technologies (45 MPa), thus reducing the pressure requirements.
[0025] In the process of forming balls using two rollers, this invention also includes judging the morphology of the pressed balls obtained by the two rollers. When the pressed balls are loose and easily broken, this invention may further include increasing the amount of water; when the pressed balls are difficult to remove from the rollers or the wet material sticks to the rollers, this invention may further include reducing the amount of water. This invention does not have a special limitation on the specific amount of water added or reduced, as long as the resulting pressed balls can be formed intact and detach from the roller pits.
[0026] After the double-roller pressing into balls, the present invention may further include sieving the pressed balls and then allowing them to stand to obtain pressed material. In this invention, the sieve used for sieving can specifically be a round-hole sieve; the aperture of the round-hole sieve can be 1 mm. In this invention, the particle size of the pressed material can be 1~4 mm, specifically 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, or 4 mm. In this invention, the standing time can be 15~40 min, specifically 15 min, 20 min, 25 min, 30 min, 35 min, or 40 min. This invention removes residual wet material that has not formed balls by sieving the pressed balls obtained from the double-roller pressing, and allows the material in the pressed balls to initially adhere by standing, preventing excessive moisture and dissolution and deformation during direct curing.
[0027] After obtaining the pressed material, the present invention cures the pressed material to obtain phosphogypsum-based fine aggregate.
[0028] In this invention, the curing temperature can be 18~22℃, specifically 18℃, 19℃, 20℃, 21℃, or 22℃; the relative humidity during curing can be ≥95%, or 96%~99.5%, specifically 95%, 96%, 97%, 98%, 99%, 99.5%, or 99.9%; the curing time can be 3~28 days, specifically 3 days, 7 days, 10 days, 15 days, 20 days, 25 days, or 28 days. This invention, through curing the obtained pressed material, allows for a slow hydration reaction within the pressed material during the curing process, forming C-(A)-SH gel and ettringite, further improving the strength of the obtained phosphogypsum-based fine aggregate. When the curing time is 3 days, the strength can reach more than 80% of the maximum strength; after curing for 28 days, the maximum strength is reached, exhibiting full activity.
[0029] This invention also provides a phosphogypsum-based fine aggregate prepared by the method described in the above technical solution. In this invention, the compressive strength of the phosphogypsum-based fine aggregate is 9.7~12.8 MPa, and can also be 10.1~11.9 MPa, specifically 9.7, 10.1, 11.9, or 12.8 MPa; the bulk density of the phosphogypsum-based fine aggregate can be 1128~1153 kg / m³. 3 Specifically, it can be expressed as 1128 kg / m 3 1142kg / m 3 1148kg / m 3 Or 1153kg / m 3 The apparent density of the phosphogypsum-based fine aggregate can be 1940~2030 kg / m³. 3 Specifically, it can be expressed as 1940 kg / m 3 1980kg / m3 2025kg / m 3 Or 2030kg / m 3 The water absorption rate of the phosphogypsum-based fine aggregate can be 4.5% to 7.2%, specifically 4.5%, 5.8%, 6.8% or 7.2%.
[0030] This invention also provides the application of the phosphogypsum-based fine aggregate described in the above-mentioned technical solution in building materials. In this invention, the building material can specifically be lightweight aggregate concrete, non-lightweight aggregate concrete, or thermal insulation wall panels. The phosphogypsum-based fine aggregate provided by this invention has high density, high compressive strength, and low water absorption, and has good application prospects in the field of building materials.
[0031] To further illustrate the present invention, the solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0032] Example 1 Figure 1 This is a flowchart illustrating the preparation of phosphogypsum-based fine aggregate in Example 1. The specific preparation steps are as follows: The undisturbed phosphogypsum was dried at 60℃ for 24 hours, and then ground in a ball mill for 5 minutes to obtain a specific surface area of 204 m². 2 / kg of phosphogypsum. The obtained phosphogypsum, calcium hydroxide, and slag are added to a forced mixer at a mass ratio of 6:3:31 and mixed for 10 minutes to obtain a powder. The water spraying device is turned on, and water is sprayed into the obtained powder while mixing to wet the powder, thus obtaining a wet material. The mass ratio of water to powder (water-cement ratio) is 1:10.
[0033] Adjust the disc rotation speed to 43 rpm, and add wet material into the roller extrusion pelletizer through the feeding port. The mass of wet material added each time is 15±2 kg. The added wet material should cover the extrusion area between the two rollers. Add more material when the wet material is almost used up. Perform roller extrusion pelletizing at 15~25℃ and 15~20MPa to obtain pressed pellets. Screen the obtained pressed pellets using a 0.75mm square-hole sieve to remove residual wet material that has not formed pellets, obtaining pressed pellets with a particle size of 1~4mm. Let them stand for 20 minutes to obtain the pressed material.
[0034] The obtained pressed material was cured for 28 days at 20℃ and relative humidity ≥95% to obtain phosphogypsum-based fine aggregate.
[0035] Figure 2 This is a picture showing the appearance of phosphogypsum-based fine aggregate after 28 days of curing. Figure 2 It can be seen that the phosphogypsum-based fine aggregate prepared by the present invention has a smooth surface, no obvious defects, good molding effect, and high sphericity.
[0036] Figure 3 Scanning electron microscope (SEM) image of phosphogypsum-based fine aggregate after 28 days of curing. Figure 3 It can be seen that the phosphogypsum-based fine aggregate obtained by the present invention is dense inside with almost no obvious pores and generates a large number of hydration products.
[0037] The obtained phosphogypsum-based fine aggregate was subjected to X-ray diffraction analysis. Figure 4 The X-ray diffraction patterns of aggregates of different particle sizes in phosphogypsum-based fine aggregates are shown in Figure 1. Figure (a) shows the curing time for 3 days, and Figure (b) shows the curing time for 28 days. Based on the X-ray diffraction patterns, the hydration products in the phosphogypsum-based fine aggregates were fitted with a full-peak diagram using the Rietveld method, and the results are shown in Table 1.
[0038] Table 1. Fitting results of full-peak diagrams for phosphogypsum-based fine aggregates of different particle sizes.
[0039] Table 1 shows the full-peak fitting results for phosphogypsum-based fine aggregates of different particle sizes. (From Table 1 and...) Figure 3 It is known that the main hydration products in phosphogypsum-based fine aggregates are ettringite and amorphous phases, which provide the main strength of the aggregates. With increasing curing time, the amount of ettringite gradually increases, improving mechanical properties. The amount of amorphous phase decreases over time, which is due to the presence of unhydrated particles in the slag, interfering with the relative amount of the amorphous phase.
[0040] Figure 5 The graphs show the TG values of aggregates of different particle sizes in phosphogypsum-based fine aggregates. Figure (a) shows the values after a curing time of 3 days, and Figure (b) shows the values after a curing time of 28 days. Figure 5 It is known that the main hydration products in phosphogypsum-based fine aggregates are C-(A)-SH gel and ettringite, which provide the main strength of the aggregates. As the curing time increases, phosphogypsum is gradually reacted, the hydration products increase, and the mechanical properties improve. As the curing time gradually increases to 28 days, the phosphogypsum-based fine aggregates will still undergo slow hydration, and the mechanical properties will gradually improve.
[0041] Table 2. Compressive strength of phosphogypsum-based fine aggregates of different particle sizes after 28 days of curing.
[0042] Table 2 shows the compressive strength of phosphogypsum-based fine aggregates with different particle sizes after 28 days of curing. As can be seen from Table 2, the compressive strength of the phosphogypsum-based fine aggregates prepared by this invention is as high as 9.7~12.8 MPa after 28 days of curing. The compressive strength of the phosphogypsum-based fine aggregates increases with the decrease of particle size.
[0043] Table 3. Individual particle strength, bulk density, apparent density, and water absorption of phosphogypsum-based fine aggregates of different particle sizes after 28 days of curing.
[0044] Table 3 shows the single-particle strength, bulk density, apparent density, and water absorption of phosphogypsum-based fine aggregates with different particle sizes after 28 days of curing. As can be seen from Table 3, the phosphogypsum-based fine aggregates prepared in this invention exhibit high single-particle strength, bulk density, and apparent density after 28 days of curing. The phosphogypsum-based fine aggregates possess excellent mechanical properties, high density, and low water absorption, making them suitable for application in building materials. The single-particle strength of the phosphogypsum-based fine aggregates increases with decreasing particle size, while the bulk density, apparent density, and water absorption decrease with decreasing particle size.
[0045] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing phosphogypsum-based fine aggregate, characterized in that, Includes the following steps: Phosphogypsum, calcium-based alkaline materials, slag, and water are mixed to obtain a wet material; The wet material is pressed into balls using two rollers to obtain pressed material; The pressed material is cured to obtain phosphogypsum-based fine aggregate; The particle size of the phosphogypsum-based fine aggregate is 1~2mm; The pressure at which the twin rollers press the balls is 15~20MPa; The mass ratio of phosphogypsum to calcium-based alkaline material is 2~2.5:1; the mass ratio of phosphogypsum to slag is 6:30~31. The ratio of the total mass of the phosphogypsum, calcium-based alkaline material, and slag to the mass of water is 10:0.9~1.
1.
2. The preparation method according to claim 1, characterized in that, The phosphogypsum has a particle size of 1~4.75mm and a specific surface area of 200~220m². 2 / kg.
3. The preparation method according to claim 1 or 2, characterized in that, The calcium-based alkaline material includes one or more of calcium hydroxide, calcium oxide, carbide slag, red mud, and alkaline slag.
4. The preparation method according to claim 3, characterized in that, The temperature at which the two rollers press the balls is 15~25℃.
5. The preparation method according to claim 1, characterized in that, The curing temperature is 18~22℃, the relative humidity is ≥95%, and the time is 3~28 days.
6. The preparation method according to claim 1, characterized in that, The process of mixing phosphogypsum, calcium-based alkaline material, slag, and water includes the following steps: Phosphogypsum, calcium-based alkaline materials, and slag are mixed to obtain a powder. Water is sprayed into the powder to obtain a wet material.
7. The preparation method according to claim 2, characterized in that, The phosphogypsum is further subjected to drying and grinding before use; The drying temperature is 60~80℃, and the time is 1200~1680min; The grinding time is 5-15 minutes.
8. The phosphogypsum-based fine aggregate prepared by the preparation method according to any one of claims 1 to 7, characterized in that, The compressive strength of the phosphogypsum-based fine aggregate is 11.9~12.8 MPa.
9. The application of the phosphogypsum-based fine aggregate according to claim 8 in building materials.
Citation Information
Patent Citations
High-density ardealite-based aggregate as well as preparation method and application thereof
CN116621482A
All-solid waste phosphogypsum-based aggregate as well as preparation method and application thereof
CN118206349A